2021
DOI: 10.1021/acs.biomac.1c00745
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Covalent Protein Modification Strategies to Facilitate Intracellular Delivery

Abstract: Protein-based therapeutics represent a rapidly growing segment of approved disease treatments. Successful intracellular delivery of proteins is an important precondition for expanded in vivo and in vitro applications of protein therapeutics. Direct modification of proteins and peptides for improved cytosolic translocation are a promising method of increasing delivery efficiency and expanding the viability of intracellular protein therapeutics. In this Review, we present recent advances in both synthetic and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 238 publications
0
31
0
Order By: Relevance
“…28,29 But due to the shortcomings of the physical methods such as inefficient, not scalable, and cytotoxic, it is hard to translate in vivo intracellular delivery of protein therapeutics. 30 With the development of nanotechnology, a new generation to replace the physical methods of delivery strategies with multiple functions (e.g., tumor targeting, deep tumor penetration, and effective cellular uptake) was come up to address these limitations.…”
Section: Strategies For Intracellular Protein Deliverymentioning
confidence: 99%
“…28,29 But due to the shortcomings of the physical methods such as inefficient, not scalable, and cytotoxic, it is hard to translate in vivo intracellular delivery of protein therapeutics. 30 With the development of nanotechnology, a new generation to replace the physical methods of delivery strategies with multiple functions (e.g., tumor targeting, deep tumor penetration, and effective cellular uptake) was come up to address these limitations.…”
Section: Strategies For Intracellular Protein Deliverymentioning
confidence: 99%
“…Hundreds of protein therapeutics have been approved by the FDA for clinical use, and five of the top ten best-selling drugs were proteins last year. 2,3 Despite the progress, all of the marketed protein drugs function extracellularly due to their limited membrane permeability. 4 Developing efficient intracellular protein transfer carriers plays an important role in the development of cytosolic protein-related biotherapeutics and biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Two major strategies have been studied to improve intracellular protein delivery: increasing the hydrophobicity of the protein and increasing the cationic charge on the protein. 5 It has previously been demonstrated that hydrophobic proteins can translocate across the cell membrane, most likely due to favorable hydrophobic interactions with the lipid bilayer. Mix et al were able to deliver an esterified green fluorescent protein (GFP) directly to the cytosol.…”
Section: Introductionmentioning
confidence: 99%